Influence of growth stage and variety on the pigment levels in Ipomoea batatas (sweet potato) leaves - Hue, S.M.; Boyce, A.N.; Somasundram, C. (2011)
The study of pigments and nutritional composition in Ipomoea batatas has been intensive, yet little studies have been conducted on their leaves. I. batatas (sweet potato) leaves which are discarded after the harvesting period can be used as a potential source of natural dye extraction due to their high level of carotenoids (particularly lutein). Selection of leaves material is dependable on factors such as leaves varieties and stages of growth developments. Variations in chlorophyll a, chlorophyll b, total carotenoids and lutein level were determined spectrophotometrically at different stages of leaves development in 6 different varieties of I. batatas leaves. Result showed that chlorophyll a, b, total carotenoids and lutein pigments increased rapidly when measured from day 1 to 7 and remained stagnant or decreased at older stages (day 15 to 18). Both the I. batatas var Oren and Biru Putih contained the highest amount of carotenoids and lutein from day 7 onwards compared to the other varieties and thus can be used as a suitable source of natural yellow dye. Â© 2011 Academic Journals.